Grand old unraveling the Republican party, Donald Trump, and the rise of authoritarianism - White, John Kenneth 1952- (University Press of Kansas, 2024)
"Building on his 2016 book, What Happened to the Republican Party?, John Kenneth White's new book proposes to explain why this happened-not just the election of Trump but the authoritarian shift in the party as a whole that led to January 6, 2021, and its aftermath. White argues that the rise of Republican authoritarianism was several decades in the making, going back to the desperation that took hold among party elites in the wake of twenty years of Democratic dominance between 1932 and 1952. White traces how a culture of conspiracy theories developed within the GOP and how the emphasis on winning at any cost created a cult of personality and a willingness to seize power by any means necessary"--
Includes bibliographical references and index. - Includes filmography
Keywords: Republican Party -- USA; Geschichte; Verschwörungstheorie; Republican Party (U.S. : 1854- ) / History; Conspiracy theories / United States / History; Contested elections / United States / History; United States / Politics and government / 1901-1953; Théories du complot / États-Unis / Histoire; Élections / Contestation / États-Unis / Histoire; États-Unis / Politique et gouvernement / 1901-1953; POLITICAL SCIENCE / Political Process / Political Parties; POLITICAL SCIENCE / American Government / Executive Branch